Low-tube-voltage selection for non-contrast-enhanced CT: Comparison of the radiation dose in pediatric and adult phantoms. Issue 1 (January 2016) - Shimonobo, Toshiaki; Funama, Yoshinori; Utsunomiya, Daisuke; Nakaura, Takeshi; Oda, Seitaro; Kiguchi, Masao; Masuda, Takanori; Sakabe, Daisuke; Yamashita, Yasuyuki; Awai, Kazuo
Highlights: In small pediatric patients low tube voltage can be applied for non-contrast CT. In adults, the radiation dose increases as the tube voltage decreases. Changes in the tube current at different tube voltages must be considered. Abstract: Purpose: We used pediatric and adult anthropomorphic phantoms to compare the radiation dose of low- and standard tube voltage chest and abdominal non-contrast-enhanced computed tomography (CT) scans. We also discuss the optimal low tube voltage for non-contrast-enhanced CT. Methods: Using a female adult- and three differently-sized pediatric anthropomorphic phantoms we acquired chest and abdominal non-contrast-enhanced scans on a 320-multidetector CT volume scanner. The tube voltage was set at 80-, 100-, and 120 kVp. The tube current was automatically assigned on the CT scanner in response to the set image noise level. On each phantom and at each tube voltage we measured the surface and center dose using high-sensitivity metal-oxide-semiconductor field-effect transistor detectors. Results: The mean surface dose of chest and abdominal CT scans in 5-year olds was 4.4 and 5.3 mGy at 80 kVp, 4.5 and 5.4 mGy at 100 kV, and 4.0 and 5.0 mGy at 120 kVp, respectively. These values were similar in our 3-pediatric phantoms (p > 0.05). The mean surface dose in the adult phantom increased from 14.7 to 19.4 mGy for chest- and from 18.7 to 24.8 mGy for abdominal CT as the tube voltage decreased from 120 to 80 kVp (p < 0.01). Conclusion: Compared to adults, the surface and center dose for pediatric patients is almost the same despite a decrease in the tube voltage and the low tube voltage technique can be used for non-contrast-enhanced chest- and abdominal scanning.